The Effects of Repeated Push Sled Sprints on Blood Lactate, Heart Rate Recovery and Sprint Times - Waller, Michael; Robinson, Tracey; Holman, Dustin; Gersick, Matthew (Journal of Sports Research, 2016)
Resisted sprinting devices have been examined for their effect on sprinting but there is limited research on sled pushing thus leaving a gap in the literature related to this topic. The current study examined the effects of varied push sled loads during repeated sprinting on blood lactate levels, heart rate recovery, and sprint times. Division II female power athletes (softball n = 5, volleyball n = 9), age 19.93 ± .83 years, body mass 70.71 ± 5.39 kg, height 170.29 ± 6.41 cm, and body fat 17.47 ± .04 %, participated in a randomized, repeated measures study. Subjects were randomly assigned to a traditional sprint condition (SPR), sprints pushing an unloaded sled (SLED), along with the following loads of 10 kg, 15 kg, 20 kg, 35 kg, 50 kg and completed each condition over a 7 week period with testing occurring once a week at the same time of day. For each condition, subjects performed 6 sprints over 20 yds with a 35 second passive recovery between each sprint with split times and total times measured. Blood lactate was obtained by a finger prick and was analyzed by a portable lactate analyzer (Accutrend® Lactate) at rest prior to the repeat sprint trials, 3 minutes and 5 minutes post intervals. The results demonstrated statistically significant differences in all mean sprint times and in peak sprint times except in 10 kg and 15 kg conditions. Statistically significant differences were observed in BLA3MIN and BLA5MIN in sprint conditions ≥ 15 kg. The results suggest that repeated push sled sprints ≥ 15 kg load may be beneficial to adapting the fast glycolytic system.